PENGEMBANGAN INSTRUMEN PENILAIAN TES BERBASIS HOTS SETTING ETNOMATEMATIKA NAGEKEO PADA MATERI SEGI EMPAT DI SISWA KELAS IV SDK SUPILAPE - Melkior Wewe; Maria Anjelina Putrini (Jurnal Ilmiah Mandalika Education (MADU), 2024)
This research aims to determine the development stage, validity, practicality and effectiveness of the ethnomathematics-based HOTS assessment instrument for class IV SDK Supilape. This research uses research and development, implementation, with the ADDIE model consisting of 5 stages: analysis, design, development, implementation, and evaluation. The subjects in this research were 15 grade IV SDK Supilape students, using quantitative descriptive analysis techniques for data analysis. The results of the development stage research were carried out in 5 stages, namely; a) analysis stage, analyzing student needs, test instruments used by teachers to obtain data related to problems and needs for developing HOTS test instruments, b) design, designing test instruments, compiling research instruments in the form of validation sheets, assessing practicality, effectiveness, and needs analysis questionnaires students, c) development, developing the product created and revising the product according to the advice of the expert team, validation by validators, d) implementation, testing the product on research subjects, assessing practicality and effectiveness by students and mathematics teachers, e) evaluation, evaluating test results try, carry out data analysis from assessing the practicality and effectiveness of the test instrument.